Mutagenicity, clastogenicity and antimutagenicity of medicinal plant tablets produced by the NSTA plant. I. Yerba buena tablets - Lim-Sylianco, C.Y; Blanco, F.R.B; Lim, C.M (1986)
Rec assay revealed that "yerba buena" tablets from NSTA Pilot Plant do not possess direct DNA damaging capacity. These tablets are not mutagenic before and after metabolic activation as shown by the Ames test and host-mediated assay respectively and they do not possess chromosome breaking capacity as shown by the micronucleus test. "Yerba buena" tablets reduced the formation of micronucleated polychromatic erythrocytes induced by dimethylnitrosamine, N-nitrosopyrrolidine and tetracycline indicating the antimutagenic activity of the tablets.